Formulation and Evaluation of Gastroretentive Tablets of Lovastatin using Hydrophilic Rate Retarding Polymers - B, Naveen Kumar (International Journal of Pharmaceutical & Biological Archive, 2014)
Formulation and Evaluation of Gastroretentive Tablets of Lovastatin using Hydrophilic Rate Retarding Polymers